Neuralgic amyotrophy with multiple hourglass-like constrictions of anterior interosseous nerve: a case report - Shi, Fangling; Zhou, Xiaoling; Li, Xueyuan (Frontiers in Neurology, 2024)
Hourglass-like constrictions (HLCs) of peripheral nerves in the upper extremity were a rare form of neuralgic amyotrophy, often characterized by the sudden onset of pain in the shoulder or arm, followed by muscle weakness and amyotrophy, with limited sensory involvement. We present a case of multiple HLCs of the anterior interosseous nerve (AIN) in a 22-year-old female with left upper arm pain, finger numbness, and limited activity for 1 month. Physical examination showed weakness of the left index flexor digitorum profundus and flexor pollicis longus, with mild hypoesthesia in the first three fingers and the radial half of the ring finger. Electromyography suggested a median nerve (mainly AIN) lesion. Ultrasonographic imaging of the median nerve shows AIN bundle swelling and multiple HLCs at left upper arm. Despite conservative treatment, which included 15 days of steroid pulse therapy, Etoricoxib, and oral mecobalamin, the patient still complained of extreme pain at night without relief of any symptoms. Operation was recommended for this patient with thorough concerns of surgical advantages and disadvantages. During surgery, a total of 7 HLCs were found in her median nerve along and above the elbow joint. Only Interfascicular neurolysis was performed because the nerve constrictions were still in the early stage. The pain was almost relieved the next day. One month after surgery, she could bend her thumb and index fingers, although they were still weak. 4 months after the surgery, she was able to bend affected fingers, with muscle strength M3 level. At the same time, her fingers had fewer numbness symptoms. There was still controversy regarding treatment strategy; however, early diagnosis and surgical treatment for nerve HLCs might be a better choice to promote nerve recovery.